A cross-sectional study on burden and predictors of obesity and anemia in school-going adolescents from Northern India - Patale, Ganesh; Rathoria, Ekansh; Singh, Saurabh Kumar; Yadav, Suresh Kumar; Lahari, Rohitash; Rathoria, Richa (International Journal of Contemporary Pediatrics, 2025)
Background: Adolescence, a period of rapid growth and high nutritional demand, faces a dual burden of malnutrition. This study assessed anemia and obesity prevalence and their demographic, dietary and anthropometric associations among school-going adolescents in India. Methods: A cross-sectional study was conducted from August 2023 to January 2025 in selected schools in Sitapur, India, enrolling 386 adolescents via multistage random sampling. Data on sociodemographic, dietary habits and clinical history were collected through structured interviews. Anthropometry (weight, height, body mass index (BMI), waist-hip ratio (WHR), mid-upper arm circumference (MUAC)) and hemoglobin levels (automated hematology analyser) were measured. Anemia and obesity were classified using WHO guidelines and CDC BMI percentiles/WHR cut-offs, respectively. Data were analyzed using SPSS v26.0; p<0.05 was considered significant. Results: The mean age was 14.19±2.63 years. Overweight and obesity prevalence were 7.8% and 30.8%, respectively, with 10.6% underweight. Central obesity was present in 45.6% (WHR). Anemia affected 32.4% and was associated with female gender (OR=2.77, p<0.001), nuclear family (B=-0.900, OR=0.41, p=0.005), vegetarian diet (B=-1.903, OR=0.15, p<0.001) and low socioeconomic status (OR=10.26, p<0.001). Obesity was linked to non-vegetarian diet (OR=2.467, p=0.009), daily fast-food intake (OR=3.323, p=0.005) and inversely associated with lower SES (B=-2.083, OR=0.124, p<0.001). No significant association was observed between BMI and anemia (p=0.591). Conclusions: High prevalence of overweight/obesity (38.6%) and anemia (32.4%), with notable coexistence, highlights the dual burden of malnutrition. Integrated school-based interventions focusing on screening, nutrition education and early management are essential to improve adolescent health in India.